THE EFFECT OF POPULATION GROWTH AND TRADE OPENNESS ON ECONOMIC GROWTH OF THE OIC COUNTRIES - Noor Syahro El Muharromy; Ilmiawan Auwalin (Universitas Airlangga, 2021)
ABSTRAKPertumbuhan ekonomi memegang peranan penting dalam menentukan keberhasilan pembangunan sebuah negara, oleh karena itu setiap negara selalu menetapkan target pertumbuhan ekonomi yang stabil dalam tujuan pembangunan. Dalam prosesnya pertumbuhan ekonomi dipengaruhi oleh berbagai factor yang dapat mendorong atau bahkan menghambat laju pertumbuhan. Penelitian ini bertujuan untuk menganalisis pertumbuhan penduduk, keterbukaan perdagangan, inflasi, nilai tukar dan investasi terhadap pertumbuhan ekonomi 40 negara anggota Organisasi Kerjasama Islam (OKI) pada tahun 2005-2019 menggunakan pendekatan kuantitatif dengan teknik analisis regresi data panel fixed effect model dan menggunakan aplikasi Eviews 11dalam mengelola data penelitian. Hasil penelitian ini menunjukkan bahwa variabel pertumbuhan penduduk dan nilai tukar memiliki hubungan signifikan dan negatif terhadap pertumbuhan ekonomi, sedangkan keterbukaan perdagangan dan investasi berpengaruh signifikan dan positif. Sedangkan investasi tidak berpengaruh signifikan pada pertumbuhan ekonomi di Negara OKI. Berdasarkan hasil penelitian ini pemerintah dan pihak terkait diharapkan dapat mengendalikan tingkat pertumbuhan penduduknya serta mendorong sektor perdagangan internasional untuk meningkatkan pertumbuhan ekonomi mengingat tingkat keterbukaan perdagangan di Negara OKI masih dibawah potensinya.Kata Kunci: Pertumbuhan Ekonomi, Pertumbuhan Penduduk, Keterbukaan Perdagangan, Organisasi Kerjasama Islam. ABSTRACTEconomic growth plays an important role in determining the success of a country's development; therefore, each country always sets a target for stable economic growth in its development goals. In the process, economic growth is influenced by various factors that can encourage or even hinder the growth rate. The purpose of this study is to analyze the effect of population growth, trade openness, inflation, exchange rates and investment on the economic growth of 40 member countries of the Organization of Islamic Cooperation (OIC) in 2005-2019 using a quantitative approach with a fixed effect model panel data regression analysis technique and using the Eviews application. 11 in managing research data. The results of this study indicate that the variables of population growth and exchange rates have a significant and negative relationship to economic growth, while trade openness and investment have a significant and positive effect. Meanwhile, investment has no significant effect on economic growth in the OIC Country. Based on the results of this study, the government and related parties are expected to control the rate of population growth and encourage the international trade sector to increase economic growth considering that the level of trade openness in the OIC is still below its potential.Keywords: Economic Growth, Population Growth, Trade Openness, Organization of Islamic Cooperation REFERENCESAbbas, Q., Nurunnabi, M., Alfakhri, Y., Khan, W., Hussain, A., & Iqbal, W. (2020). The role of fixed capital formation, renewable and non-renewable energy in economic growth and carbon emission: A case study of Belt and Road Initiative project. Environmental Science and Pollution Research, 27(36).Abubakar, A. B. (2015). Impact of International trade on economic growth in India. International Journal of Financial Research, 6(3). https://doi.org/10.5430/ijfr.v6n3p163Ali, S., Ali, A., & Amin, A. (2013). The impact of population growth on economic development in Pakistan. Middle East Journal of Scientific Research, 18(4), 483–491. https://doi.org/10.5829/idosi.mejsr.2013.18.4.12404Aprianto, N. E. K. (2017). Kebijakan distribusi dalam pembangunan ekonomi Islam. Jurnal Hukum Islam, 14(2), 73. https://doi.org/10.28918/jhi.v0i0.693Badan Kependudukan dan Keluarga Berencana. (2012). Analisis Dampak Laju Pertumbuhan Penduduk dan Kualitas Hidup Manusia di Indonesia.Baharumshah, A. Z., Slesman, L., & Wohar, M. E. (2016). Inflation, inflation uncertainty, and economic growth in emerging and developing countries: Panel data evidence. Economic Systems, 40(4), 638–657. https://doi.org/10.1016/j.ecosys.2016.02.009Banerjee, R. (2012). Population growth and endogenous technological change: Australian economic growth in the long run. Economic Record, 88(281), 214–228. https://doi.org/10.1111/j.1475-4932.2011.00784.xBarguellil, A., Ben-Salha, O., & Zmami, M. (2018). Exchange rate volatility and economic growth. Journal of Economic Integration, 33(2), 1302–1336.Becker, G. S., Glaeser, E. L., & Murphy, K. M. (1999). Population and economic growth. The American Economic Review, 89(2).Bucci, A., & Raurich, X. (2016). Population and economic growth under different growth engines. German Economic Review, 1–30. https://doi.org/10.1111/geer.12092Chirwa, T. G., & Odhiambo, N. M. (2016). Macroeconomic determinants of economic growth: A review of international literature. South East European Journal of Economics and Business, 11(2), 33–47. https://doi.org/10.1515/jeb-2016-0009Destek, M. A. (2016). Natural gas consumption and economic growth: Panel evidence from OECD countries. Energy, 114, 1007–1015. https://doi.org/10.1016/j.energy.2016.08.076Dzian, M., H. Paluš., & Parobek, J. (2020). The impact of globalisation on the Slovak timber trade. Sustainability of Forest-Based Industries in the Global Economy - Proceedings of Scientific Papers, 45–49.Ertimi, B. E., Albisht, E. M., & Oqab, B. A. (2016). The Impact of corruption on economic growth in oic countries the impact of corruption on economic growth in OIC Countries. International Journal of Economics and Finance, 8(9). https://doi.org/10.5539/ijef.v8n9p91Furqani, H. (2017). Consumption and morality: Principles and behavioral framework in Islamic economics. Journal of King Abdul Aziz University: Islamic Economics, 30, 89–102.Grauwe, P. D., & Schnabl, G. (2008). Exchange rate stability, inflation, and growth in (South) Eastern and Central Europe. Review of Development Economics, 12(3), 530–549. https://doi.org/10.1111/j.1467-9361.2008.00470.xGul, H., Mughal, K., & Rahim, S. (2012). Linkage between monetary instruments and economic growth. Universal Journal of Management and Social Sciences, 2(5).Haller, A. (2012). Concepts of economic growth and development. Challenges of crisis and of knowledge. Economy Transdisciplinarity Cognition, 15(1).Halwani, H. (2012). Ekonomi internasional dan globalisasi ekonomi. Surabaya: Ghalia Indonesia.Hasan, M. S. (2010). The long-run relationship between population and per capita income growth in China. Journal of Policy Modeling, 32(3), 355–372. https://doi.org/10.1016/j.jpolmod.2009.09.005Hatmanu, M., Cautisanu, C., & Ifrim, M. (2020). The impact of interest rate, exchange rate and european business climate on economic growth in Romania: An ARDL approach with structural breaks. Sustainability (Switzerland), 12(7). https://doi.org/10.3390/su12072798Hayati, M. (2016). Investasi menurut perspektif ekonomi Islam. IKONOMIKA Jurnal Ekonomi dan Bisnis Islam, 1(April), 66–78.Ikechi, K. S., & Emmanuel, N. C. (2015). Capital expenditures and gross fixed capital formation in Nigeria. Research Journal of Finance and Accounting, 6(12), 188–198.Ikit, Artiyanto, H., & Saleh, M. (2018). Jual beli dalam perspektif ekonomi Islam. Yogyakarta: Penerbit Gava Media.Ismail, P. Z. (2012). Teori ekonomi. Bandung: Dharma Ilmu.Jhingan, M. L. (2000). Ekonomi pembangunan dan perencanaan. Jakarta: Rajawali Press.Khalid, M. A. (2016). The impact of trade openness on economic growth in the case of Turkey. Research Journal of Finance and Accounting, 7(10).Khan, M. S., & Ssnhadji, A. S. (2013). Threshold effects in the relationship between inflation and growth. IMF Staff Papers, 48(1), 1–21.Kharis, M. M. (2011). Pengaruh faktor-faktor kependudukan terhadap pertumbuhan ekonomi di kabupaten Pemalang. Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Koirala, S. (2018). An analysis of the impact of real effective exchange rate on economic growth of Nepal. Pravaha, 24(1), 206–216. https://doi.org/10.3126/pravaha.v24i1.20239Mankiw, G. N. (2011). Makroekonomi. Terjemahan dari Macroeconomics 6th (ed.); 6th ed.).Milani, F., & Park, S. H. (2015). The Effects of Globalization on Macroeconomic Dynamics in a Trade-Dependent Economy : the Case of Korea. Economic Modelling, 48.Nurul Huda, dkk. (2017). Ekonomi Pembangunan Islam. Kencana Prenada Media Press.Peterson, E. W. F. (2017). The role of population in economic growth. SAGE Open, 7(4). https://doi.org/10.1177/2158244017736094Razmi, M. J., & Refaei, R. (2013). The effect of trade openness and economic freedom on economic growth: The case of middle east and East Asian countries. International Journal of Economics and Financial Issues, 3(2), 376–385.Rudiawan, H., & Meirinaldi. (2019). Dampak faktor-faktor makro ekonomi terhadap pertumbuhan produk domestik bruto Indonesia. Jurnal Ekonomi, 21(1). https://doi.org/10.37721/je.v21i1.535Sakinah, S. (2015). Investasi dalam Islam. IQTISHADIA: Jurnal Ekonomi & Perbankan Syariah, 1(2), 248. https://doi.org/10.19105/iqtishadia.v1i2.483Sugiyono. (2016). Metode penelitian kuantitatif kualitatif dan R&D. Bandung: CV. Alfabeta.Sukirno, S. (2013). Makro ekonomi teori pengantar. Jakarta: Raja Grafindo Persada.Sulistiawati, R. (2012). Pengaruh investasi terhadap pertumbuhan ekonomi dan penyerapan tenaga kerja serta kesejahteraan masyarakat di provinsi di Indonesia. Jurnal Ekonomi Bisnis dan Kewirausahaan, 3(1), 29–50.Todaro, M. P., & Smith., S. C. (2013). Pembangunan ekonomi. Jakarta: Erlangga.Tsen, W. H., & Furuoka, F. (2005). The relationship between population and economic growth in Asian Economies. Asean Economic Bulletin, 22(3), 314–330. https://doi.org/10.1355/ae22-3eUmaru, H., A, A. N., & Davies, N. O. (2018). The effects of exchange rate volatility on economic growth of West African english-speaking countries. International Journal of Academic Research in Accounting, Finance and Management Sciences, 8(4), 131–143. https://doi.org/10.6007/IJARAFMS/v8-i4/5470Vorlak, L., Abasimi, I., & Fan, Y. (2019). The impacts of exchange rate on economic growth in Cambodia. International Journal of Applied Economics, Finance and Accounting, 5(2), 78–83. https://doi.org/10.33094/8.2017.2019.52.78.83Yalçınkaya, Ö., Hüseyni, İ., & Çelik, A. K. (2017). The impact of total factor productivity on economic growth for developed and emerging countries: A second-generation panel data analysis. The Journal of Applied Economic Research, 4, 404–417. https://doi.org/10.1177/0973801017722266Yao, W., Kinugasa, T., & Hamori, S. (2013). An empirical analysis of the relationship between economic development and population growth in China. Applied Economics, 45(33), 37–41. https://doi.org/10.1080/00036846.2013.795284Zaky, M., Asyadi, M., Zainodin, M., Saja, M., Nawi, S. M., Firdaus, M., & Erna, N. (2015). Managing investment in the light of quran and sunnah: Textual analysis. Procedia Economics Anf Finance, 31(15), 380–386. https://doi.org/10.1016/S2212-5671(15)01213-7